Symbolic computation of solutions for three generalized nonlinear partial differential eQuations by using the tanh method - Salas, Alvaro H.; Gómez, Cesar A. (Revista Colombiana de Computación, 2009)
Three nonlinear partial differential equations, namely, the standard KdV equation, the Boussinesq equation and the generalized fifthorder KdV equation are considered here from of point the view of construct exact solutions for them. The equations that we consider here are in its most general form. New exact solutions which include periodic and soliton solutions are formally derived by using the tanh method. The programming language Matematica is used.